2011
DOI: 10.1029/2010ja016014
|View full text |Cite
|
Sign up to set email alerts
|

Angular dependence of pump-induced bottomside and topside ionospheric plasma turbulence at EISCAT

Abstract: [1] We experimentally observe the location and angular size of the high-frequency (HF) radio window in the bottomside ionosphere, which permits radio wave propagation to the topside ionosphere, with high angular resolution at the European Incoherent Scatter (EISCAT) facility. HF pump-induced ion line enhancements were observed by the EISCAT UHF incoherent scatter radar on the ionospheric bottomside and topside. The radar zenith angle was scanned in small steps in the magnetic meridian. The HF pump duty cycle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
1
12
2
Order By: Relevance
“…Observations of bottom and topside enhancements in the ionospheric F region were reported for the first time by Isham et al (1990). The radio window associated with the conversion from O mode to Z mode lies around the Spitze or critical angle (Ginzburg, 1970) and for a horizontally stratified ionosphere; it is of the order of 1 • , as recently reported by Kosch et al (2011) for the Tromsø F region. However, for an ionosphere containing significant electron density perturbations, the conversion to Z mode is possible also at other angles than the critical angle, Mishin et al (2001).…”
Section: Discussionsupporting
confidence: 49%
“…Observations of bottom and topside enhancements in the ionospheric F region were reported for the first time by Isham et al (1990). The radio window associated with the conversion from O mode to Z mode lies around the Spitze or critical angle (Ginzburg, 1970) and for a horizontally stratified ionosphere; it is of the order of 1 • , as recently reported by Kosch et al (2011) for the Tromsø F region. However, for an ionosphere containing significant electron density perturbations, the conversion to Z mode is possible also at other angles than the critical angle, Mishin et al (2001).…”
Section: Discussionsupporting
confidence: 49%
“…Previous analyses of OZ conversion near the X = 1 condition have assumed straight isocontours of f pe , with the option of investigating how conversion depends on the angles separating the isocontour direction, the incident O-mode propagation direction, and the B 0 axis [Mjolhus, 1984;Budden, 1985;Muldrew, 1993;Nordblad and Leyser, 2010;Kosch et al, 2011;Cannon et al, 2016]. The significance of Figures 3, 6, and 7 is that radiation from an ionospheric heater can encounter a variety of isocontour directions near X = 1, necessitating a variety of conversion geometries over the latitude range where OZ conversion may occur.…”
Section: 1002/2016rs006190mentioning
confidence: 99%
“…The concept of “radio window” whereby electromagnetic radiation converts from one cold‐plasma mode to another has aroused interest in various areas of research in ionospheric radio science [ Budden , ; Mjolhus , ]. Ionospheric modification following conversion from O mode to Z mode has been of particular interest [see Muldrew , ; Nordblad and Leyser , ; Kosch et al , ; Cannon et al , , and references therein]. A nexus in plots of cold‐magnetoplasma refractive index of the O and Z propagation modes has been identified as a critical concept in the sequence of processes occurring as O‐mode radiation makes its way from powerful high frequency (HF) ground transmitters to the ionospheric F 2 layer where the Z‐mode wave packets either undergo absorption at the upper oblique resonance or suffer total reflection, depending on the F 2 layer density.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancements of the backscattered power in the ion and plasma lines of ISR measurements in the ionosphere, due to high‐power HF wave pumping, have been observed many times (e.g., Ganguly & Gordon, ; Isham et al, ; Isham, Rietveld, et al ; Isham, Hagfors, et al ; Kosch et al, ; Rietveld et al, ). Isham et al () reported ion‐line enhancements at the topside and bottomside of the F‐region observable during the first 10‐s period after heating on in magnetic zenith.…”
Section: Introductionmentioning
confidence: 99%
“…Nordblad and Leyser () also suggest that L‐mode propagation through heater induced radio windows can not be ruled out as an explanation for the Isham, Rietveld, et al () observations. In an experiment studying the angular extent of the radio window in 2004, Kosch et al () observed clear topside enhancements during a low duty cycle (3.3%), heating experiment pointed in a direction 9 ∘ south of zenith. They present observations indicating the location of the bottomside radio window to be around 7 ∘ –8 ∘ south of zenith, arguing that this can be explained by a tilt in the ionosphere, that was observed in the Dynasonde data during the experiment.…”
Section: Introductionmentioning
confidence: 99%